2012
DOI: 10.5617/njhe.227
|View full text |Cite
|
Sign up to set email alerts
|

Use of Primary Care Emergency Services in Norway: Impact of Birth Country and Duration of Residence

Abstract: Abstract:Objective: In Norway, the General Practitioner Scheme was established in 2001. Satisfaction with the system is generally high. However, people often choose to visit community-based emergency wards (EW) for routine care instead. The aim of this paper is to describe which factors influence the choice of seeking care at the EW. Design, setting, and patients: Prior national research on utilization patterns has been based mostly on surveys showing a low response rate. By using merged register data, we anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…Regarding all health problems, differences between immigrants’ and natives’ use of emergency primary health care (EPC) have been documented, though service use among immigrants varies by factors such as age, country background, immigration reason, length of stay and socioeconomic status [ 2 , 6 9 ]. A recent, national-level Norwegian study found that contact rates at EPC services were lower for immigrants as a whole compared with Norwegians, though higher among specific groups [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding all health problems, differences between immigrants’ and natives’ use of emergency primary health care (EPC) have been documented, though service use among immigrants varies by factors such as age, country background, immigration reason, length of stay and socioeconomic status [ 2 , 6 9 ]. A recent, national-level Norwegian study found that contact rates at EPC services were lower for immigrants as a whole compared with Norwegians, though higher among specific groups [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Oslo (the capital of Norway), as well as Bergen and Drammen, have the highest density of immigrants. Scandinavian research indicates a diverging picture regarding utilization of EW services by immigrants compared to non-migrants [ 8 , 9 , 10 , 11 ]. A Norwegian study concluded that high rates of EW use among immigrants are related to inadequate access to GP services, suggesting that new residents are not well informed about the organizational structure of the primary health sector [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…A Norwegian study concluded that high rates of EW use among immigrants are related to inadequate access to GP services, suggesting that new residents are not well informed about the organizational structure of the primary health sector [ 11 ]. Another study has demonstrated that immigrants use the EW more often than non-migrants, and that the differences in EW use among immigrant groups are smaller than the differences between genders in these groups, confirming that the duration of residence influences the likelihood of visiting the EW and that this impact is greatest during the first years after arrival [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Such factors can include consanguinity, (Stoltenberg et al 1998), nutrition (Essen et al 2000b), and the utilisation of health care services (Goth and Godager 2012;Grytten, Skau, and Sørensen 2013). At least in the short run, women from countries with good access to health care services might be expected to be more frequent users of these services in the host country.…”
Section: Post-arrival Effectsmentioning
confidence: 99%
“…At least in the short run, women from countries with good access to health care services might be expected to be more frequent users of these services in the host country. Indeed, two studies have shown that women's utilisation of health care services varies by the source country (Goth and Godager 2012;Grytten, Skau, and Sørensen 2013).…”
Section: Post-arrival Effectsmentioning
confidence: 99%